2021
DOI: 10.48550/arxiv.2102.10021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Kalman Filtering

Beren Millidge,
Alexander Tschantz,
Anil Seth
et al.

Abstract: The Kalman filter is a fundamental filtering algorithm that fuses noisy sensory data, a previous state estimate, and a dynamics model to produce a principled estimate of the current state. It assumes, and is optimal for, linear models and white Gaussian noise. Due to its relative simplicity and general effectiveness, the Kalman filter is widely used in engineering applications. Since many sensory problems the brain faces are, at their core, filtering problems, it is possible that the brain possesses neural cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…active inference agents, can perform laser-based localization and navigation tasks. The results obtained in the localization experiment, where we compared our approach against a state-of-the-art alternative (particle filter), show the potential of predictive stochastic neural filtering in robot localization, and estimation in general [6,15]. Furthermore, the navigation experiment showcased how to compute actions as a dual filtering process.…”
Section: Discussionmentioning
confidence: 90%
“…active inference agents, can perform laser-based localization and navigation tasks. The results obtained in the localization experiment, where we compared our approach against a state-of-the-art alternative (particle filter), show the potential of predictive stochastic neural filtering in robot localization, and estimation in general [6,15]. Furthermore, the navigation experiment showcased how to compute actions as a dual filtering process.…”
Section: Discussionmentioning
confidence: 90%
“…However, it is unclear how BayesPCN's locally conjugate Bayesian weight update can be realized in the brain unlike GPCN's Hebbian weight update arising from gradient descent. Nevertheless given that the Kalman filter can be approximated by gradient descent Millidge et al [2021b] and the fact that BayesPCN's weight update is related to the mixture Kalman filter, there may be a biologically plausible way of approximating BayesPCN's write. In addition, there are similarities between BayesPCN's diffusion-based f orget and the synaptic homeostasis hypothesis [Cirelli and Tononi, 2022], where during sleep the synaptic weight strengths are decreased on average to facilitate future learning.…”
Section: Discussionmentioning
confidence: 99%
“…Other models explicitly compare deterministic and probabilistic implementations to predictive coding [16]. Gradient based predictive coding, the approach we will use here, is largely biologically plausible as all optimization can be described with Hebbian updates rules [5,17]. Gradient based predictive coding is deterministic based on the nature of its updates without explicit sampling.…”
Section: Related Workmentioning
confidence: 99%
“…There are many conceptual similarities between the state-of-the-art in machine learning, namely deep neural networks and the error back-propagation algorithm, and predictive coding models. Work that aims at directly connecting these fields, however, is still relatively sparse [4,5,6,7,8]. Recently, it has been suggested that gradient based predictive coding, when it includes precision estimations, directly implements a form of Natural Gradient Descent, i.e.…”
Section: Introductionmentioning
confidence: 99%